Informal caregivers’ knowledge about the prevention of pressure injuries in dependent homebound patients. Cross-sectional study with a psychometric phase - Urian-Peña, Yina Teresa; Fuentes-González, Nieves; Quemba-Mesa, Mónica Paola (Universidad y Salud, 2023)
Introduction: Skin lesions associated with home care affect patient quality of life and have negative effects on informal caregivers. Objective: To determine informal caregivers’ knowledge regarding the prevention of pressure injuries in dependent homebound patients in Tunja, Colombia. Materials and methods: Descriptive cross-sectional study with a psychometric phase. Experts from the COCU-LCRD 23 performed facial validation, which assessed coherence, relevance, and pertinence of each item. The application of the instrument was carried out on population samples based on household census, after which its reliability was calculated. Results: Facial validation showed moderate concordance, requiring improvements in the wording of the Kappa de Fleiss items: 0.4582 (p=0.000). Most of caregivers were women (83.3%), with an average age of 40 years (SD±13.39) and 43.3% of them have a knowledge index of 83.33, which includes aspects such as hydration, position changes, among others. The adjusted version of the questionnaire reached a Cronbach’s alpha of 0.6322. Conclusions: Informal caregivers have low education levels. Also, they are not knowledgeable and have limited experience regarding preventive care of dependent people at risk of pressure ulcers.